Crypt Suzette [large type] - Corrigan, Maya (Corrigan, Maya. Five-ingredient mystery., 2019)
"Suzette Cripps has been occupying a spare bedroom at Val's granddad's house while she takes classes in this Maryland Eastern Shore town-but she's always seemed a little secretive and fearful, and any talk about her past is a closed book. After winning the costume contest at the Halloween-themed bookstore party, Suzette is mowed down by a hit-and-run driver-and Val and her grandfather start to wonder whether it was really an accident or if someone was after Suzette. Granddad is a little distracted by his new enterprise as a ghost-buster, but as Val talks to Suzette's coworkers and fellow creative writing students, she grows more convinced that the dead woman's demons weren't imaginary-and that she needs to rip the mask off a killer ..."--Publisher description.